Towards a comprehensive approach to climate policy, sustainable infrastructure, and finance - Céline Bak; Amar Bhattacharya; Ottmar Edenhofer; Brigitte Knopf (Economics: The Open-Access, Open-Assessment E-Journal, 2017)
The authors propose a policy package of low-carbon growth stimulation through a steep increase in sustainable infrastructure, mobilizing sustainable finance, and adoption of carbon pricing to simultaneously achieve the objectives of the Paris Agreement and the Sustainable Development Goals.
Keywords: D62; E62; H21; H22; 330; G-20; Paris Agreement; climate change; infrastructure; carbon pricing; green finance